2009
DOI: 10.1111/j.1755-3768.2008.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of reading speed after providing of low vision aids in patients with age‐related macular degeneration

Abstract: ABSTRACT.Purpose: Age-related macular degeneration (AMD) is the most common cause of severe visual impairment, including loss of reading ability, among elderly persons in developed countries. The aim of the present study was to evaluate reading ability before and after providing of appropriate low vision aids. Methods: Five hundred and thirty patients with different stages of AMD (age 82 ± 8 years) were included in this retrospective study. All patients underwent a standardized ophthalmological examination inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 18 publications
3
68
0
9
Order By: Relevance
“…12 In another study of 530 cases with ARMD, 94% of patients were able to read after obtaining LVAs, but it is clear that satisfying acuity does not guarantee efficient reading in practical life. 14 Leat et al reported that although 75% of the patients surveyed could read 1M (approximately newsprint size) print in the clinic, only 35% reported that they could read normal print at home, which indicated that patients that can "see to read" do not necessarily read regularly at home. 3 It is well known that visual acuity is not a good measure of patient's satisfaction with low vision rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…12 In another study of 530 cases with ARMD, 94% of patients were able to read after obtaining LVAs, but it is clear that satisfying acuity does not guarantee efficient reading in practical life. 14 Leat et al reported that although 75% of the patients surveyed could read 1M (approximately newsprint size) print in the clinic, only 35% reported that they could read normal print at home, which indicated that patients that can "see to read" do not necessarily read regularly at home. 3 It is well known that visual acuity is not a good measure of patient's satisfaction with low vision rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane Review concluded that electronic devices tended to be preferred to optical ones. 5 More recently, a retrospective review by Nguyen et al 22 of 530 vision rehabilitation patients reported improved reading speeds in patients who were prescribed low vision aids; 42% of the group received video camera magnifiers. It is not stated whether there was a difference between those receiving video camera magnifiers or other aids.…”
Section: Discussionmentioning
confidence: 99%
“…Visual acuity and the reading speed of the visually impaired children can be improved by low vision devices and their training. 6,7 Thus quality of life of the visually impaired children gets bett er by low vision devices. However prescripti on of low vision devices depends upon the individuals.…”
Section: Introductionmentioning
confidence: 99%